Obstetrical and Non-Obstetrical Factors toward Uterine Prolapse Occurrence in Ulin General Hospital Banjarmasin on Januari – December 2017 - Yohanes Adhitya Prakasa Sukoco Putra; Eko Suhartono; Pribakti Budinurdjaja (Berkala Kedokteran, 2019)
Abstract: Uterine prolapse is a gynecological disease in women that emerge patients physically and psychologically. Uterine prolapse is defined as an uterus herniation inside or outside vagina as the result of the ligament and fascia failure that retain the uterus in its actual place. This research was to identify obstetrical and non-obstetrical factors in uterine prolapses occurrence in Ulin General Hospital Banjarmasin on period January until December 2017 using case control approach. The total sample was 80 medical record samples, which divided into 40 medical record samples of patient with uterine prolapse and 40 medical record samples of patient without the occurrence of uterine prolapse. The results using chi square analysis obtained non-obstetrical factors: age >60 years old (OR 6.67: 95%CI 2.44-18.21), BMI > 30 (OR 3.10: 95%CI 1.24-7.71), menopause (OR 21.00: 95%CI 6.11-72.18); and non-obstetrical factors: parity >4 / multiparity (OR 13.78: 95%CI 4.71-40.28), macrosomia (OR 7.15: 95%CI 2.65-19.34), vaginal delivery (OR 28.78: 95%CI 7.41-111.79). The results of logistic regression obtained non-obstetrical factors: age > 60th (Exp B 4.21 and sig. 0.004), menopause (Exp B 1.12 and sig. 0.001), and multiparity (Exp B 2.35 and sig. 0.016). The results of this analysis obtained that obstetrical and non-obstetrical factors were related to uterine prolapse occurrence, and the dominant factor was age > 60 years old, so it could be concluded that there was significant factor between obstetrical and non-obstetrical factors on uterine prolapse occurrence in Ulin General Hospital Banjarmasin. Keywords: uterine prolapse, obstetrical factor, non-obstetrical factor